Histological, immunocytochemical and ultrastructural study of thyrotrophs in buffalo (Bubalus bubalis) - KHAN, MASSARAT; SAIGAL, R P; SETHI, R S (The Indian Journal of Animal Sciences, 2011)
The study was conducted on the hypophysis cerebri from 56 buffaloes including male calves aged 1 week to 4 months and adult females in different phases of the reproductive cycle. Various differential staining methods and immunocytochemical methods were used on paraffin sections to localize and detail the thyrotrophs. Ultra thin sections from adenohypophysis pars distalis of 4 anilnals were used for the ultrastructural studies. The thyrotrophs were dispersed singly and localised within the follicles/acini, distributed maximum in caudal aspect (21.19%) of the pars distalis and decreased in central (17.37%) and dorsal (170/0) regions followed by rostral (16.680/0) and lateral (16.51%) regions, being minimum in the ventral (14.65%) regions. Average diaIneter of thyrotrophs was 8.7Â±O.28 mm, which increased considerably from 8.1 mm at 1 week of age to 9.3 mm and 10.7 mm in adults and females in advance pregnancy, respectively. These cells constituted 17.42% of the adenohypophysial cell population. In the cyclic females, they varied from 15.47 to 15.81% in proportions and, were maximum (23.32%) during 3 nl0nths of pregnancy. Of the chromophils they comprised 32.680/0 in 1-week-old male calf and decreased with age to 13.890/0 in adults. Ultrastructurally, the thyrotrophs appeared variably shaped as irregularly elongated or polygonal with SOUle processes in male calf, and irregularly oval or elongated in adult females. They occurred singly wedged between other granulated cell types and contained relatively fewer, smaller and spherical electron dense secretary granules scattered all over the cytoplasm. The average size of the secretary granules was larger in calf as compared to adult cyclic females but maximum during pregnancy. Â